Current and Emerging Medical Treatments for Uterine Fibroids - Chwalisz, Kristof; Taylor, Hugh (Seminars in Reproductive Medicine, 2017)
Uterine fibroids (leiomyomata) are common uterine neoplasms that are often associated with detrimental symptoms, such as heavy menstrual bleeding, dysmenorrhea, and pressure-related symptoms, which often lead to surgical intervention, including hysterectomy. Although our understanding of the pathophysiology of uterine fibroids, particularly their dependency on progesterone and the role of growth factors, has increased during the past two decades, the medical options currently approved by the United States Food and Drug Administration are limited and are only used for short-term symptom management. A long-term, safe, and effective treatment is not yet available in the United States. However, emerging medical treatments that are currently under clinical development, including progesterone receptor modulators and oral gonadotropin-releasing hormone antagonists, offer hope of new long-term medical therapies for symptomatic uterine fibroids as an alternative to surgery. Herein, we discuss the current and emerging medical therapies for fibroids based on evidence from randomized clinical trials.
Keywords: uterine fibroids; progesterone receptor modulators; oral GnRH antagonists